Japanese newspaper compounds : - Kikuoka, Tadashi (Charles E. Tuttle, 1970)
Half-baked methods are not sufficient in learning to read Japanese publications particularly Japanese newspapers. What is needed is a well-organized, graded program of study draw up by authorities. This book is a major contribution to the one thousand most important character compounds appearing in Japanese newspapers and their definitions, inorder of descending frequency.